ANALYSIS OF THE IMPACT ASSESSMENT APPROACHES OF VOCATIONAL EDUCATION AND TRAINING RESULTS IN EUROPEAN UNION MEMBER STATES - Tentere, Grieta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Work based learning (WBL), introduced in Vocational education and training (VET) system, promises to increase economic competitiveness and development of the knowledge-based economy in Latvia. WBL aims to provide knowledge and understanding regarding types of work in a chosen occupation, build specific competencies needed for work and motivate young people to acquire 21st Century skills for smoother transition from education to sustainable employment and development of their professional career. WBL is closely linked to life-long guidance at all stages of decision making: future occupation or workplace, upskilling or reskilling, acquisition of transferable skills or career management skills. Ensuring effective integration of life-long guidance with WBL three elements are essential: engagement before entering WBL programmes; achievement within WBL to encourage participation and successful completion; transition to work after graduating VET supported by personalised follow-up and on-going career support.WBL is a new approach for most European Union Member States (EU MS), ensuring a positive impact on employment perspectives for students by providing skills demanded by employers and an acceptable level of VET quality, allowing the VET graduate to find a job quickly or obtain a well-paid job. The European Quality Assurance Reference Framework for VET (EQAVET) is an EU instrument to improve the systems of Quality Assurance (QA) in VET, based on a quality cycle and on using performance indicators and self-assessment. EQAVET proposes indicators that could be utilized to monitor VET provision and for peer reviews between EU MS. Most indicators serve as VET performance indicators, however some characterize VET impact on the graduate’s transition to work. Analysis of the positive and negative aspects of VET QA indicators could be the basis for development of WBL and support life-long learning strategies.